Phylogeny and gene expression of the complete NITRATE TRANSPORTER 1/PEPTIDE TRANSPORTER FAMILY in Triticum aestivum. (28th May 2020) - Wang, Huadun; Wan, Yongfang; Buchner, Peter; King, Robert; Ma, Hongxiang; Hawkesford, Malcolm J
Abstract : This first systematic characterization of the whole wheat NPF gene family contributes to a better understanding of this large gene family in wheat and lays the foundation for further functional analysis. Abstract: NPF genes encode membrane transporters involved in the transport of a large variety of substrates including nitrate and peptides. The NPF gene family has been described for many plants, but the whole NPF gene family for wheat has not been completely identified. The release of the wheat reference genome has enabled the identification of the entire wheat NPF gene family. A systematic analysis of the whole wheat NPF gene family was performed, including responses of specific gene expression to development and nitrogen supply. A total of 331 NPF genes (113 homoeologous groups) have been identified in wheat. The chromosomal location of the NPF genes is unevenly distributed, with predominant occurrence in the long arms of the chromosomes. The phylogenetic analysis indicated that wheat NPF genes are closely clustered with Arabidopsis, Brachypodium, and rice orthologues, and subdivided into eight subfamilies. The expression profiles of wheat NPF genes were examined using RNA-seq data, and a subset of 44 NPF genes (homoeologous groups) with contrasting expression responses to nitrogen and/or development in different tissues were identified. The systematic identification of gene composition, chromosomal locations, evolutionary relationships, and expression profiles contributes to a better understanding of the roles of the wheat NPF genes and lays the foundation for further functional analysis in wheat.